The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.3354/ame027057
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton fecal pellets, marine snow and sinking phytoplankton blooms

Abstract: Zooplankton fecal pellets have long been thought to be a dominant component of the sedimentary flux in marine and freshwater ecosystems, but that view is changing. The last 2 decades have seen publication of > 500 studies using sediment traps, which reveal that zooplankton fecal pellets often constitute only a minor or variable proportion of the sedimentary flux. Substantial proportions of this flux are from organic aggregates ('marine snow') of various origins, including phytoplankton blooms, which sediment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
464
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(497 citation statements)
references
References 201 publications
(260 reference statements)
17
464
1
5
Order By: Relevance
“…3). The cylindrical faecal pellets were probably derived from copepods and euphausiids, and the ovoid faecal pellets may originate from small copepods or larvaceans (Gonzalez, 1992;Turner, 2002;Wilson et al, 2008;Wexels Riser et al, 2008).…”
Section: Composition Of Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The cylindrical faecal pellets were probably derived from copepods and euphausiids, and the ovoid faecal pellets may originate from small copepods or larvaceans (Gonzalez, 1992;Turner, 2002;Wilson et al, 2008;Wexels Riser et al, 2008).…”
Section: Composition Of Particlesmentioning
confidence: 99%
“…Bishop, 1989;Buesseler, 1991;Newton, 1995, 1999;Buesseler and Boyd, 2009). Of particular interest is determining the conditions under which phytoplankton can be directly exported via physical flocculation and sinking, without passing through higher trophic levels that engender respiration losses of POC (Michaels and Silver, 1988;Alldredge and Jackson, 1995;Turner, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Sinking rates ( ) of organic material from PP and SP were adopted from Turner (2002) SP carcasses are assumed equivalent to detritus entangled in sinking marine snow and respired as such (Iversen and Ploug, 2010;Tang and Elliott, 2013). We assumed a consumption rate similar to that of sinking faecal pellets ( _ , from Eq.…”
Section: _66mentioning
confidence: 99%
“…Numerous field studies (> 500) using sediment traps have revealed that zooplankton fecal pellets often constitute a minor portion of the sedimentary flux, much less than what would be expected from the zooplankton abundances and expected fecal pellet production rates (González & Smetacek 1994, Turner 2002. A reduced vertical flux is often attributed to recycling and repackaging of the fecal pellets by coprophagous (ingestion of pellets) copepods (Smetacek 1980, Bathmann et al 1987, González & Smetacek 1994, González et al 1994a, Lane et al 1994, Urban-Rich et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced vertical flux is often attributed to recycling and repackaging of the fecal pellets by coprophagous (ingestion of pellets) copepods (Smetacek 1980, Bathmann et al 1987, González & Smetacek 1994, González et al 1994a, Lane et al 1994, Urban-Rich et al 1999. Also, coprorhexy (fragmentation of pellets) and coprochaly (loosening of pellets) may increase the residence time of fecal material in the water column (Lampitt et al 1990, Noji et al 1991) and make it subject to enhanced microbial degradation (Turner 2002), thus accelerating recycling of fecal pellet material in the water column.…”
Section: Introductionmentioning
confidence: 99%